2020
DOI: 10.21608/svuijm.2020.48334.1028
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Coblation Adenoidectomy and Conventional Adenoidectomy

Abstract: Back ground: the classic surgical technique performed with an adenoid curette or an adenotome has recently developed by the introduction of the endoscopic sinus surgery Objectives: to compare the safety and efficacy of coblation adenoidectomy versus conventional curettage adenoidectomy.Patients and methods: This study was conducted on 50 patients who came to outpatient clinics in the Otolaryngology department, of age group between 4-14 years with adenoids hypertrophy from February 2019 to February 2020.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Group A was associated with a significant decrease in resolution days. Aref et al [13] reported a significant decline in recovery days in association with the coblation technique compared to the conventional one [2.6 vs. 4.7 days in the two groups respectivelyp < 0.001], which coincides with the findings of this study.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Group A was associated with a significant decrease in resolution days. Aref et al [13] reported a significant decline in recovery days in association with the coblation technique compared to the conventional one [2.6 vs. 4.7 days in the two groups respectivelyp < 0.001], which coincides with the findings of this study.…”
Section: Resultssupporting
confidence: 91%
“…Operative time was significantly decreased in Group C in comparison with the other two groups. In line with our findings, Aref et al [13] reported a substantial increase in operating time associated with coblation versus the standard method [p < 0.001]. It had mean values of 14.2 and 11.1 minutes in the coblation and conventional groups respectively.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations